2012
DOI: 10.1021/bc200330m
|View full text |Cite
|
Sign up to set email alerts
|

Bioconjugate of Lysozyme and the Antibacterial Marine Sesquiterpene Quinone Avarone and Its Derivatives

Abstract: A conjugate of lysozyme with avarone, a bioactive sesquiterpene quinone of marine origin, and its three derivatives, was synthesized. MALDI TOF mass spectral analysis and tryptic digestion showed that the only residue in lysozyme that was modified by all derivatives was lysine 97. The identity of the residue was in full correlation with the prediction obtained by molecular modelling. All bioconjugates preserved most of the enzymatic activity of lysozyme. The melting point of the conjugates was slightly increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Additionally, it was reported that mono-6- O -formyl-β-CD is a suitable substrate for such reactions. The presented approach also proved a comparable effect on the enzymatic activity of the lysozyme with other methods used for the preparation of lysozyme conjugates with different compounds [ 34 ]. Tethering of the β-CD moieties to the lysozyme does not significantly alter its secondary or tertiary structures as indicated by circular dichroism measurements, but does affect its hydrodynamic parameters and thermal stability.…”
Section: Resultsmentioning
confidence: 88%
“…Additionally, it was reported that mono-6- O -formyl-β-CD is a suitable substrate for such reactions. The presented approach also proved a comparable effect on the enzymatic activity of the lysozyme with other methods used for the preparation of lysozyme conjugates with different compounds [ 34 ]. Tethering of the β-CD moieties to the lysozyme does not significantly alter its secondary or tertiary structures as indicated by circular dichroism measurements, but does affect its hydrodynamic parameters and thermal stability.…”
Section: Resultsmentioning
confidence: 88%
“…For example, conjugation of lysozyme with water‐soluble compounds, such as glucose, stearic acid monoester, or PEG, exhibited no reduction in lysozyme enzymatic activity 37. 41 In contrast, procedures that involve the use of 20 % DMSO in the reaction mixture for the conjugation of lysozyme with water‐insoluble avarone derivatives resulted in a 23 % decrease in lysozyme biological activity 42. The minor effect of conjugation conditions on lysozyme activity involving the use of a highly organic (95 % DMSO) reaction medium and freeze‐drying demonstrated the possibility of the broader application of both the “in solution” and “in solid state” methods for lysozyme modification with hydrophobic ligands 24.…”
Section: Resultsmentioning
confidence: 99%
“…The minor effect of conjugation conditions on lysozyme activity involving the use of a highly organic (95 % DMSO) reaction medium and freeze‐drying demonstrated the possibility of the broader application of both the “in solution” and “in solid state” methods for lysozyme modification with hydrophobic ligands 24. 25, 41, 42 Furthermore, it seems that the observed decrease in protein activity for LZ‐( 1 ) compared with that for t LZ could be attributed to the modification itself and not the modification procedure. The ability of LZ‐( 1 ) to hydrolyze bacterial cell walls decreased by 63.3 % compared with t LZ (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the acetoxy group at C-3 has a positive contribution to the antibacterial activity. The improved activity may be attributed to the acetoxy group, which can help this compound traverse the phospholipid bilayer of bacterial cells . However, this modification decreased the inhibitory activity against S. albus , S. aureus , and E. coli .…”
Section: Resultsmentioning
confidence: 99%